Multiple extreme climatic events strengthen selection for earlier breeding in a wild passerine. (8th May 2017) - Marrot, Pascal; Garant, Dany; Charmantier, Anne
Abstract : Global climate warming results in an increase in mean temperatures and in the frequency of extreme climatic events (ECEs), which could both strongly impact ecosystems and populations. Most studies assessing the impact of global warming on ecosystems have focused on warming trends while neglecting ECEs. In particular, the effects of multiple ECEs on fitness, and their consequences for selection, are still missing. Here we explored the effects of daily extreme rainfalls, as well as the occurrence of extremely hot and cold days, on clutch size and laying date in a wild blue tit population ( Cyanistes caeruleus ) monitored over 25 years. During the nestling phase (8–15 days old), the number of fledglings in a brood was negatively correlated with extremely hot days. The presence of extremely hot days between days 8 and 15 was also associated with an increase in the strength of selection acting on laying date, independently of mean temperature trends during the same period: when 10% of broods in the population experienced this type of ECE, selection for earlier breeding increased by 39%. Our results represent a unique quantification of the impact of multiple ECEs on the fitness landscape and emphasize their role as climatic drivers of selection. This article is part of the themed issue 'Behavioural, ecological and evolutionary responses to extreme climatic events'.